Interactions of charged domain walls and oxygen vacancies in BaTiO3: a first-principles study. (August 2018) - Gong, J.J.; Li, C.F.; Zhang, Y.; Li, Y.Q.; Zheng, S.H.; Yang, K.L.; Huang, R.S.; Lin, L.; Yan, Z.B.; Liu, J.-M.
Abstract: Ferroelectric domain walls have been promised for some potential applications due to their unique properties. In particular, the electrical conductivity of charged domain walls (DWs) allows a new dimension to ferroelectric functionalities. In this work, we construct two representative types of charged DWs, i.e. head-to-head (HH) wall and tail-to-tail (TT) wall, and employ the first-principles method to study the electronic structure of these charged walls in BaTiO3 and the interactions between them and oxygen vacancies. It is revealed that the HH walls show the n -type conductivity, but the TT walls show the p -type conductivity. While embedded oxygen vacancies attract the TT wall and repel the HH wall, the interaction between the walls and oxygen vacancies depends on the vacancy occupation. This interaction enhances the conductivity of HH walls and reduces the conductivity of TT walls, and in particular a TT wall in binding with oxygen vacancies will drive the transition of p -type wall conductivity into n -type wall conductivity. The interaction of these walls with oxygen vacancies is discussed using the electrostatic model. This work represents a comprehensive understanding of electrical transport of charged DWs in ferroelectrics and possible roadmaps for manipulation. Graphical abstract: Image 1 Highlights: This is an innovative research on how the properties of domain walls are affected by charged defects. The effects of oxygen vacancies on the morphology, electronic structure, and conductivity of domain walls are investigated. Our results indicate that the conductivity of the domain wall can be effectively tailored by oxygen vacancies.